2007
DOI: 10.1016/j.bbrc.2007.01.097
|View full text |Cite
|
Sign up to set email alerts
|

The Prp19/Pso4 core complex undergoes ubiquitylation and structural alterations in response to DNA damage

Abstract: Prp19/Pso4, a U-box containing E3 ligase, has a demonstrated role in pre-mRNA splicing, but has also been implicated in both yeast and mammalian cells as having a direct role in DNA damage processing. In this report we provide further evidence in support of this latter assertion. We show that hPrp19 forms an ubiquitylated oligomeric species that is resistant to disruption by SDS gel electrophoresis under nonreducing conditions suggesting that is mediated by a thiolester between ubiquitin and a cysteine residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 27 publications
7
55
0
Order By: Relevance
“…The Prp19 antibody detected additional bands (most prominently in S-100) (Fig. 2B, lanes 1,2) that may correspond to previously described ubiquitinated forms of Prp19 (Lu and Legerski 2007). Consistent with that report, which showed that Prp19 ubiquitination disrupts its association with other complex members, these modified forms failed to cofractionate with other PRP19C subunits on Mono Q (data not shown), suggesting that the modification disrupts interactions between Prp19 and other complex subunits.…”
Section: U2af65 Interacts With the Prp19c In Vitro And In Vivosupporting
confidence: 78%
“…The Prp19 antibody detected additional bands (most prominently in S-100) (Fig. 2B, lanes 1,2) that may correspond to previously described ubiquitinated forms of Prp19 (Lu and Legerski 2007). Consistent with that report, which showed that Prp19 ubiquitination disrupts its association with other complex members, these modified forms failed to cofractionate with other PRP19C subunits on Mono Q (data not shown), suggesting that the modification disrupts interactions between Prp19 and other complex subunits.…”
Section: U2af65 Interacts With the Prp19c In Vitro And In Vivosupporting
confidence: 78%
“…Possible reasons for the increased sensitivity of the particular cell line should first be sought among the functions of those proteins. Interestingly, TGM2 and PRP19 have previously been shown to promote cancer cell survival when overexpressed [39,40], which is consistent with our results. Namely, high level of carbonylation has been shown to inactivate protein function, thus, rendering the cells deprived of the particular protein activity (similarly to a conditional mutant).…”
Section: Discussionsupporting
confidence: 83%
“…HPso4 is a human homolog of the PS04/PRP19 gene in S. cerevisiae that has pleiotropic functions in DNA recombination and errorprone repair (15,16,18,28,(33)(34)(35)(36)(37)(38). Specific role(s) for Pso4 in DSB repair is not known; however, it has been identified as a component of the nuclear matrix (20).…”
Section: Discussionmentioning
confidence: 99%
“…Because the Pso4 is a part of the pre-mRNA splicing complex consisting of Pso4, Cdc5L, Plrg1, and Spf27 (17), Metnase may interact with a portion of the pre-mRNA splicing complex. In fact, the presplicing complex was shown to link to DNA repair through a direct physical interaction of Cdc5L with WRN, a DSB repair factor deficient in Werner syndrome (18,28). It is possible that the MetnasehPso4 interaction is only a part of the much bigger complex that participates in DSB repair in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation